THE INFLUENCE OF MODERN AGRICULTURAL TECHNOLOGY ON THE PRODUCTIVITY OF LOCAL FOOD CROPS - Sulfiana Sulfiana; Andi Tenri Fitriyah; Baharuddin Baharuddin (INJOSEDU: International Journal of Social and Education, 2025)
In an effort to increase agricultural productivity, especially for local food crops, modern agricultural technology plays an important role. The research method conducted in this study uses the literature research method. The results show that modern technology in agriculture significantly increases the effectiveness of production through optimisation of water and soil use, as well as through the development of better crop varieties. Information technology assists farmers in making decisions based on accurate data, strengthening their position in the face of uncertain market and environmental conditions. However, cost, knowledge and infrastructure constraints are barriers to the adoption of these technologies.